Exploring Reflective English Language Teaching Programs in the Framework of TPACK - Choiril Anwar; Abdurrahman Faridi; Issy Yuliasri; Hendi Pratama; Kurniawan Yudhi Nugroho (Universitas Negeri Semarang, 2022)
Technology, pedagogy, and subject knowledge are all integrated into the teaching framework known as TPACK (Technological Pedagogical and Content Knowledge). This framework has not been widely used by English teachers in Indonesia to help pupils learn English. This study intends to investigate, evaluate, and thoroughly discuss English language education programs within the context of TPACK. The descriptive qualitative method was employed in this study. The information was gathered through a review of the literature on English language instruction utilizing the TPACK (Technological Pedagogical and Content Knowledge) paradigm. The collected literature data were then thoroughly compared, assessed, critiqued, and concluded after thorough analysis. The information demonstrates reflective programs for teaching English as a second language that combine and integrate technology, pedagogy, and content, including methods and activities for learning English as well as methods for assessing language proficiency. The findings of this study are anticipated to enhance the general knowledge and instructional abilities of Indonesian teachers, particularly those who teach English.